The Aesthetics of Wayang Klithik as A Study Of Local Cultural Wisdom in Wonosoco Village, Kudus Regency - Anisa Ussolihah; Yusuf Falaq (JURNAL PENDIDIKAN IPS, 2023)
The purpose of this study was to determine the aesthetic values of Wayang Klithik in Wonosoco Village, Kudus Regency. In this study, researchers used a qualitative descriptive method. Data collection techniques were carried out by conducting field studies in the Wonosoco Village, Kudus Regency. The data obtained were then analyzed descriptively. The results of the study show that the figures and characters played in the Wayang Klithik show have important values in life, as well as the elements and principles of wayang Klithik art which are the aesthetic value of Wayang Klithik itself. Wayang Klithik has essential and important values in supporting public knowledge and as an effort to preserve the art of Wayang Klithik. The aesthetic values contained in wayang klithik also have evil and good values, which can be used to be applied in everyday life or in society. As well as efforts to actualize the elements and principles in the art of Wayang Klithik can be used as material for development in increasing harmony. As well as being able to solve environmental problems and be able to develop various natural potentials in the environment.